ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN JASA AUDIT AKUNTAN PUBLIK PADA KOPERASI DI KABUPATEN SIAK - Wahyudi Wahab; Amir Hasan; Andreas Andreas (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
This study aims to analyze and examine the influence of business volume, liquidityratio, gearing ratio and audit cost to public accountant audit requests oncooperatives in Siak Regency. The population in this study are all cooperativebusiness entities in Siak Regency until 2015. The sample is 71 cooperativesselected based on purposive sampling method. The type of data used is quantitativedata using a secondary source. Data analysis technique used in this research islogistic regression analysis. The results showed that the variable volume of thebusiness influence on the demand for audit services public accountant. While theratio of liquidity ratio, gearing ratio and audit cost does not affect the demand ofaudit services public accountant.